Triphenylphosphine‐Functionalized Core‐Cross‐Linked Micelles and Nanogels with a Polycationic Outer Shell: Synthesis and Application in Rhodium‐Catalyzed Biphasic Hydrogenations. Issue 16 (16th February 2021) - Wang, Hui; Vendrame, Lorenzo; Fliedel, Christophe; Chen, Si; Gayet, Florence; D'Agosto, Franck; Lansalot, Muriel; Manoury, Eric; Poli, Rinaldo
Abstract: Unimolecular amphiphilic nanoreactors with a poly(4‐vinyl‐ N ‐methylpyridinium iodide) (P4VPMe + I − ) polycationic outer shell and two different architectures (core‐cross‐linked micelles, CCM, and nanogels, NG), with narrow size distributions around 130–150 nm in diameter, were synthesized by RAFT polymerization from an R0 ‐4VPMe + I − 140 ‐ b ‐S50 ‐SC(S)SPr macroRAFT agent by either chain extension with a long (300 monomer units) hydrophobic polystyrene‐based block followed by cross‐linking with diethylene glycol dimethacrylate (DEGDMA) for the CCM particles, or by simultaneous chain extension and cross‐linking for the NG particles. A core‐anchored triphenylphosphine (TPP) ligand functionality was introduced by using 4‐diphenylphosphinostyrene (DPPS) as a comonomer (5–20 % mol mol −1 ) in the chain extension (for CCM) or chain extension/cross‐linking (for NG) step. The products were directly obtained as stable colloidal dispersions in water (latexes). After loading with [RhCl(COD)]2 to yield [RhCl(COD)(TPP@CCM)] or [RhCl(COD)(TPP@NG)], respectively, the polymers were used as polymeric nanoreactors in Rh‐catalyzed aqueous biphasic hydrogenation of the model substrates styrene and 1‐octene, either neat (for styrene) or in an organic solvent (toluene or 1‐nonanol). All hydrogenations were rapid (TOF up to 300 h −1 ) at 25 °C and 20 bar of H2 pressure, the biphasic mixture rapidly decanted at the end of the reaction (<2 min), the Rh loss was negligible (<0.1 ppm in the recovered organic phase), and the catalyst phase could be recycled 10 times without significant loss of catalytic activity. Abstract : Pretty polly : Stable latexes of size‐controlled spherical and unimolecular polymers, made of a cross‐linked and phosphine‐functionalized hydrophobic core and a poly( N ‐methyl‐4‐vinylpyridinium) shell, are efficient nanoreactors for rhodium‐catalyzed hydrogenation under aqueous biphasic conditions with excellent recyclability and negligible levels of leaching.